Structure and Application of ATDP Suite for Electronic System States Detection and Evolution Operator Restoration - Magda, I.I.; Paschenko, A.V.; Shapova, l I.M.; Novikov, V.E. (Радиофизика и радиоастрономия, 2002)
Structure and peculiarities of the Adaptive Testing Data Processing software Suite (ATDP Suite) are presented. It is applied for dynamic characteristics restoration from experimental time series of nonlinear and unstable electronic system. Basic methods realized in ATDP Suite are demonstrated. Application of ATDP Suite for electromagnetic tests of microwave receivers demonstrated the possibility to analyze and interpret the dynamic characteristics of complex nonlinear system.